2014
DOI: 10.1002/14651858.cd010382.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Non-pharmaceutical management of respiratory morbidity in children with severe global developmental delay

Abstract: Non-pharmaceutical management of respiratory morbidity in children with severe global developmental delay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 86 publications
0
17
0
4
Order By: Relevance
“…Further, there are also ongoing reviews, which may address some of these gaps in evidence. A number of relevant Cochrane review protocols were identified: non-pharmaceutical management of respiratory morbidity in children with severe global developmental delay (Winfield et al 2013); clozapine for psychotic disorders in adults with intellectual disabilities (Paul & Ayub 2013); and risperidone for disruptive behaviour disorders in children with intellectual disabilities (Bezuidenhout et al 2012). A series of National Institute for Health Research (NIHR) rapid systematic reviews are also being carried out, including reviews on diabetes in adults with intellectual disability; ischaemic cardiovascular disease including hypercholesterolaemia in adults with intellectual disability; sexual health in adults with intellectual disability; cancer screening in people with intellectual disabilities; and thyroid disorders (A.…”
Section: Limitationsmentioning
confidence: 99%
“…Further, there are also ongoing reviews, which may address some of these gaps in evidence. A number of relevant Cochrane review protocols were identified: non-pharmaceutical management of respiratory morbidity in children with severe global developmental delay (Winfield et al 2013); clozapine for psychotic disorders in adults with intellectual disabilities (Paul & Ayub 2013); and risperidone for disruptive behaviour disorders in children with intellectual disabilities (Bezuidenhout et al 2012). A series of National Institute for Health Research (NIHR) rapid systematic reviews are also being carried out, including reviews on diabetes in adults with intellectual disability; ischaemic cardiovascular disease including hypercholesterolaemia in adults with intellectual disability; sexual health in adults with intellectual disability; cancer screening in people with intellectual disabilities; and thyroid disorders (A.…”
Section: Limitationsmentioning
confidence: 99%
“…Systematic reviews of systematic reviews point to limited evidence concerning postural care even when populations and interventions are broadly defined (Effgen & McEwen, 2008;Novak et al, 2013;Ryan, 2012). Systematic reviews, most commonly relating to people with cerebral palsy, have generally found insufficient high-quality evidence for the effectiveness of a range of postural care interventions (Bouwhuis, van der Heijden-Maessen, Boldingh, Bos, & Lankhorst, 2015;Katalinic et al, 2010;Kolman, Ruzbarsky, Spiegel, & Baldwin, 2015;Legg, Davies, Raich, Dettori, & Sherry, 2014;Prabhu, Swaminathan, & Harvey, 2013;Winfield, Barker, Turner, & Quin, 2014). However, limited evidence suggests that special-purpose adaptive seating systems may improve activities and participation for those with cerebral palsy (Gross Motor Functioning Classification System (GMFCS) IV and V) (Angsupaisal, Maathuis, & Hadders-Algra, 2015); there are indicative findings for an effect of bony surgery in stabilizing the hip in severe cerebral palsy (Bouwhuis et al, 2015); and hip surveillance involving standardized radiological screening of the hip even in children with no symptoms has been found to be effective in reducing hip dislocation in children with cerebral palsy (Dobson, Boyd, Parrott, Nattrass, & Graham, 2002;Gordon & Simkiss, 2006;Hägglund et al, 2014;Novak et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…. .expected to last at least 12 months (unless death intervenes) Involves either several different organ systems or one organ system severely enough to require specialty paediatric care Medically fragile children 51 Dependent on technology for survival Neuromuscular disorders 52 Disorders that involve injury or dysfunction of peripheral nerves or muscle Children with severe global developmental delay 47 Significant intellectual disability and severe motor impairment Extremely limited functional movement Dependent upon others for all activities of daily living Bakke et al 7 Neurological disorders but no significant mental deficiencies Buratti et al 10 Severe psychomotor and mental retardation Danielson and Emmens 13 Non-ambulatory Severe psychomotor and mental impairment Elliott 14 Profoundly, irreversibly neurologically damaged Will never be able to speak, walk, sit up, or feed themselves Intellectual abilities extremely limited Hauer 17 Non-verbal Severe impairment of the CNS Hauer and Solodiuk 18 Severe global impairment of the CNS Khoshoo et al 22 Profound developmental delay Neuromuscular impairment Non-verbal and wheelchair-bound Lind et al 24 GOS score III and IV Mahant et al 26 GMFCS level III-V McCrea et al 29 Profound developmental impairment Requires constant care Cannot mobilize Very limited possibilities for communication Mergler et al 31,32 Moderate or severe intellectual disability (IQ <55) GMFCS level IV or V Orel et al 35 GMFCS level V Pinnington and Hegarty 36,37 Quadriplegic distribution of athetosis and/or spasticity Associated impairments in visual perception and learning Roka et al, 38 Sun et al 44 from chronic disorders. Thirty-three of the articles referred to patients with CNS disorders only, while five included both patients with disorders of the CNS and PNS.…”
Section: What This Paper Addsmentioning
confidence: 99%